Psychometrics New Insights in the Diagnosis of Mental Disorders - Misciagna, Sandro (IntechOpen, 2023)
Psychometrics is the science of assessing and measuring mental capacities and processes, which are constructs not easily observed directly. It is concerned with objective measurement of cognitive functions, characteristics of personality, emotions, behaviour, socio-educational qualities, and mental disorders. This book provides a comprehensive overview of psychometrics and its use in assessing psychological disorders. Chapters discuss the history of psychometrics and its theoretical bases and psychometric methodologies for assessing dementia, mental health, and more.